Humoral immune response, bacterial recovery and time lesions in mice geneticaly selected for high and low antibody production and in outbreed Balb/c mice face to Leptospira interrogans sorovar icterohaemorrhagiae. - Marinho, W.; Langoni, H.; Oliveira, S. L.; Carreira, R.; Perri, SHV; Luvizoto, M. C. (Revista Pesquisa Veterinaria Brasileira, 2003)
The aim of the present work was to. evaluate the association among the kinetics of humoral immune response, the recovery of viable leptospiras and the intensity of the tissue lesions in mice selected for high (H) and low (L) production of antibodies (selection IV-A) and in mice from the outbreed Balb/c line, inoculated with pathogenic Leptospira interrogans serovar icterohaemorrhagiae. The H and L lines showed modifications in some steps of the immune response, mainly in relation to the macrophagic activity, representing extreme phenotypes found in heterogeneous natural populations. Mice were sacrificed in eight moments after the infection. Analysis of the results revealed that from the 7th day after the infection, on line H mice presented antibodies titles significantly higher as compared to the L line mice, maintaining the multispecific effect Balb/c line mice showed intermediate results between the two lines. Antibodies production worked as a limiting factor to the infection, because when a greater leptospiras recovery was obtained, at the initial phase of the infection, the titles of antibodies were elevated. Inflammatory and degenerative process led to similar lesions in the organs of infected mice. Only a variation in the degree of tissue compromising was observed according to the line. H line mice showed more extensive lesions than L and Balb/c lines mice. For the Balb/c line mice, the lesions were moderate. As a rule, H and Balb/c mice lines showed a Th2 profile of immune response, with higher indexes of antibody production and gravity of the lesions, while L line mice presented a Th1 profile of immune response.
Keywords: leptospirosis; humoral immune response; bacterial recovery; lesions; mice genetically selected; Balb/c